Socializing the Value of Religious Moderation as A Foundation For Student Character Building at State Senior High School 2 Tuban - Kulsum, Umi; Syafi'i, Imam; Yasin, Muhammad; Syafi'i, Muhammad Imam; Samingan, Samingan (Interdisciplinary Explorations in Research Journal, 2026)
This Community Service Program aims to strengthen students’ understanding of religious moderation, foster tolerance and inclusivity, and reinforce national commitment through character education at State Senior High School 2 Tuban. The program was motivated by the increasing signs of intolerance among students and the urgent need to promote pluralism and harmony in educational settings. The activity employed an educative-participatory approach, combining seminars, interactive discussions, reflective sessions, and interfaith simulations involving students from diverse religious backgrounds. Data were collected through participatory observation, reflective questionnaires, and documentation. The results indicate a significant improvement in students’ conceptual understanding of religious moderation, from perceiving it merely as tolerance to recognizing it as a framework of justice, balance, social responsibility, and anti-extremism. Students also demonstrated greater openness, empathy, and respect toward religious differences in their daily interactions. Furthermore, the program strengthened students’ national commitment by instilling the awareness that loving the homeland and maintaining social harmony are integral expressions of religious practice. Overall, this Community Service Program activity demonstrated that experience-based, participatory learning effectively internalizes the values of religious moderation. It is recommended that similar programs be sustained and integrated into school curricula to cultivate tolerant, inclusive, and nationally minded students.